Penentuan Kondisi Optimum Waktu Aging dan Temperatur Pengeringan Pada Sintesis Silika Xerogel dengan Bahan Dasar Natrium Silikat dari Silika Alam - Elvina Yulistia Erwan; Budhi Oktavia (Jurnal Periodic Jurusan Kimia UNP, 2022)
Abstract — Silica is one kind of porous material that is suited to adsorben. In the synthesis process, silica gel can be produced using a sol-gel method based on the sodium silicate (Na2SiO3), which is prepared by an acid. The project of this research is to establish optimum conditions in aging time and gel-drying temperatures to produce a broad surface and pore size for silica xerogel. Based on the iod's absorption of variations in aging time (14, 16, 18, 20 and 24 hours) and drying temperatures (60, 70, 80, 90 and 100°C) give the most absorption to optimum conditions of aging time at 18 hours and drying temperatures of 70°C. The presence of XRD pattern leads to amorphous nature structures that dilate at one peak in 2θ = 22.545°, which indicates synthesis of silica xerogel with a basic sodium silicate obtained from natural silica was successfully made and highly pure. Keywords — Silica, Sodium Silicate, Silica xerogel